Inovasi Dakwah Ala Ustadz Hanan Attaki (Studi Kasus Kajian Sharing Time “Rahasia Merubah Takdir: Jodoh, Rezeki, Sukses”) - Aziza, Fathia Salsabilla; Basit, Abdul (IQTIDA : Journal of Da'wah and Communication, 2025)
This study analyzes the form of da’wah innovation and its impact in the Sharing Time study titled “The Secret to Changing Destiny: Soulmate, Fortune, and Success.” The research is driven by the limited number of contemporary da’wah studies that explore humanist and contextual approaches in conveying religious messages in the digital era. Using a qualitative descriptive case study and supported by literature review, data were collected through observation and documentation, including articles, journals, and books as secondary sources. The findings reveal that Ustadz Hanan Attaki’s da’wah innovation goes beyond sharia and aqidah by delivering messages centered on truth, peace, and appreciation of differences. His communication style is both emotional and engaging, allowing him to connect with a diverse audience effectively. This approach represents a contextual, inclusive, and reflective model of da’wah suited to today’s digital society. The da’wah messages align with Abdul Basit's theory in Filsafat Dakwah, which emphasizes the elements of truth, peace, and respect for diversity. The study concludes that the Sharing Time content positively influences audiences by fostering acceptance and deeper understanding of Islamic values delivered in a relatable and reflective manner.